1995
DOI: 10.1042/bj3070595
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a defined spatial arrangement of hyaluronate in the central filament of cartilage proteoglycan aggregates

Abstract: Aggregates of proteoglycans from the Swarm rat chondrosarcoma reassembled in vitro have been studied by rotary-shadowing electron microscopy, and shown to be similar to native structures that have never been dissociated [Mörgelin, Engel, Heinegård and Paulsson (1992) J. Biol. Chem. 267, 14275-14284]. A hyaluronate with defined chain length (HAshort) has now been prepared by autoclaving high-Mr hyaluronate and fractionation to a narrow size distribution by gel filtration. Proteoglycan monomers, core protein, hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
0
3

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 41 publications
4
36
0
3
Order By: Relevance
“…In electron micrographs one sees fine thread-like structures (Fig. 8) that extend laterally from the core protein and are consistent in appearance with that of glycosaminoglycan chains visualized in other proteoglycans (35,36). Although these appear to arise from sites throughout the core protein, some of those seen near the globular region may in fact represent chondroitin sulfate chains with attachment sites in the C-terminal half of the proteoglycan but that follow the core protein before reaching out into the surrounding space (as has been observed previously in the case of aggrecan (35)).…”
Section: Discussionmentioning
confidence: 99%
“…In electron micrographs one sees fine thread-like structures (Fig. 8) that extend laterally from the core protein and are consistent in appearance with that of glycosaminoglycan chains visualized in other proteoglycans (35,36). Although these appear to arise from sites throughout the core protein, some of those seen near the globular region may in fact represent chondroitin sulfate chains with attachment sites in the C-terminal half of the proteoglycan but that follow the core protein before reaching out into the surrounding space (as has been observed previously in the case of aggrecan (35)).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the osmotic swelling pressure of the pericellular matrix is increased when more proteoglycan is present. The presence of proteoglycans would also act to stiffen a network of hyaluronan by effectively shortening the hyaluronan chain as it wraps around the globular G1 domain [17]. When excess proteoglycan is added to the coat, the pore size of the pericellular matrix is decreased, with particles 0.3 microns or larger excluded [18].…”
Section: Pericellular Matrix Structurementioning
confidence: 99%
“…When excess proteoglycan is added to the coat, the pore size of the pericellular matrix is decreased, with particles 0.3 microns or larger excluded [18]. Link proteins stabilize the interaction between hyaluronic acid and proteoglycans [19][20][21] and have been shown to have a shortening effect on the length of hyaluronan that is similar to the proteoglycan [17]. Others have shown that adding an excess of link proteins can cause fragmentation or disruption of hyaluronan networks [22].…”
Section: Pericellular Matrix Structurementioning
confidence: 99%
“…sist of an alternating array of cLP and aggrecan molecules along a central hyaluronan filament (20). Therefore, aggregates (potentially containing new members of the HAPLN family) in which other CSPGs substitute for aggrecan might contribute to the structural integrity of many different tissues.…”
mentioning
confidence: 99%